The Development of Theme Instrument Based Test for The IV Grade of Elementary School in Margorejo District Pati - Septiningsih, Ana Sholihatin; Sumaryanto Flotentinus, Totok; Liesnoor Setyowati, Dewi (Journal of Research and Educational Research Evaluation, 2018)
This study motivated the lack of teacher's capability to apply the 2013 curriculum , so some teachers are less able to develop the independent test instrument. They depens on the LKS. Beside that, teachers are formulating question for examination without considering the indicator or analyzing basic competency that will be achieved students. This research is to develop valid standard instrument, reliable and effective use. This research is a development instrument with R & D modify the Ball & Gall approach. Test validation of the contents of use v'aiken by rating experts, to determine the validation and reliability of the empiric ie with analysis correlation point biserial and kuder richadson (KR-20). The results of validation of the contents of the instrument test-based theme by experts worth use. While the trial court of about developed a total of 30 items about a valid as much as 26 item about. So with reliability in the trial court range 0,89-0,91 with high category. While the test of effecticity, based on the analysis of the questionnaire with 6 of respondents primary school teacher and 28 items questionnaire, get a score of 497 with an average 82,83 by effective category. Based on the results of these studies, the theme-based test instruments developed valid, reliable and effective to use. This research is useful for teachers as a reference and learning materials in measuring the daily assessment of student learning outcomes.